Effects of Micronutrient Fortification, Baking Temperature, and Baking Time on Sensory Acceptance of Butter Cookies - Indriani, Widya; Sebastian, Fammela; Muslimatun , Siti (Jurnal Gizi dan Pangan, 2023)
This research aims to evaluate the effect of multiple-micronutrient fortification, baking temperature, and baking time on the sensory acceptance of butter cookies. Unfortified and fortified cookies with 3.2% (w/w) multiple-micronutrient mix were baked with different treatments: 170°C for 15 minutes and 190 °C for 9 minutes. Untrained adult female panelists (n=50) did a sensory test using a 9-point hedonic scale. Interaction between treatments significantly affected texture and aroma (p<0.05). Cookies fortified with micronutrients baked at 190°C had a lower mean hedonic score for texture (5.90±1.91) and aroma (6.54±1.61) among other treatments (p<0.05). These findings indicate that micronutrient fortification and baking profile affect the aroma and texture acceptance of butter cookies.